Language and Thought in Hildegard of Bingen's Visionary Trilogy: Close and Distant Readings of a Thinker's Development. - Gussem, Jeroen De; Wouters, Dinah (Parergon, 2019)
By combining the methods of distant reading (computational stylistics) and close reading, the authors discuss the development of language and thought in Hildegard of Bingen's visionary works (Sciuias, Liber uite meritorum and Liber diuinorum operum). The visionary trilogy, although written over the course of three decades, raises the impression of a monolithic and seemingly unchanging voice. Moving beyond this impression, the interdisciplinary analysis presented here reveals that the trilogy exhibits interesting differences at the word level which cannot simply be explained through external historical circumstances (e.g. manuscript transmission or different secretaries). Instead, the results raise pertinent questions regarding the trilogy's internal development in didactic method, style, and philosophy.